Projeto de transformador de imped?ncia de radiofreq??ncia com controle da faixa de passagem - Ferreira J?nior, Antonio Alves (2006)
ABSTRACT: This work presents a preliminary study about RF wideband impedance transformers devices, usually applied to electronic circuits. These devices are used in inter-stage coupling of amplifier chains, in hybrid circuits, signals combiners and dividers, baluns, special measurement conectors, etc.. By combining the concepts of the conventional transformer and transmission line transformer, wideband transformers are obtained. These devices can work in a wide frequency band with low insertion loss. The device unun proposed by Ruthroff was studied and it proved to have better efficiency when the impedance transformation ratio is 1 for 4. The design techniques, the measurement procedures and the theoretical models are presented. Computational tools are used to simulate the analytical response (MATLABr) and the software of radiofrequency and microwaves developed by Agilent Technologies Co. (ADSr) was applied to simulate the numerical response. With the RF vetorial network analyzer equipment it was determined the experimental response and the corresponding results were compared.